Photosynthetic performance of rocket (Eruca sativa. Mill.) grown under different regimes of light intensity, quality, and photoperiod. - Naif Ali Elmardy (Public Library of Science (PLoS), 2021)
In recent years, much effort has been devoted to understanding the response of plants to various light sources, largely due to advances in industry light-emitting diodes (LEDs). In this study, the effect of different light modes on rocket (Eruca sativa. Mill.) photosynthetic performance and other physiological traits was evaluated using an orthogonal design based on a combination between light intensity, quality, and photoperiod factors. Some morphological and biochemical parameters and photosynthetic efficiency of the plants were analyzed. Plants grew in a closed chamber where three light intensities (160, 190, and 220 μmol m-2 s-1) provided by LEDs with a combination of different ratios of red, green, and blue (R:G:B- 7:0:3, 3:0:7, and 5:2:3) and three different photoperiods (light/dark -10/14 h, 12/12 h, and 14/10 h) were used and compared with white fluorescent light (control). This experimental setup allowed us to study the effect of 9 light modes (LM) compared to white light. The analyzes performed showed that the highest levels of chlorophyll a, chlorophyll b, and carotenoids occurred under LM4, LM3, and LM1, respectively. Chlorophyll a fluorescence measurement showed that the best effective quantum yield of PSII photochemistry Y(II), non-photochemical quenching (NPQ), photochemical quenching coefficient (qP), and electron transport ratio (ETR) were obtained under LM2. The data showed that the application of R7:G0:B3 light mode with a shorter photoperiod than 14/10 h (light/dark), regardless of the light intensity used, resulted in a significant increase in growth as well as higher photosynthetic capacity of rocket plants. Since, a clear correlation between the studied traits under the applied light modes was not found, more features should be studied in future experiments.